Determination of Selenium in Thioridazine Hydrochloride by Differential Pulse Anodic Stripping Voltammetry - MODARES TEHRANI, ZOHREH; FARAHANI, ZOHREH; MOHAJER, AFSHIN; MOFIDI, JAMSHID (Asian Journal of Chemistry, 2010)
In present studies, the ability of anodic stripping voltammetry (ASV) on hanging mercury drop electrode (HMDE) has been investigated by studying the different influencing parameters. The proposed method, based on anodic stripping voltammetry of CuSe(Hg) at hanging mercury drop electrode provides a simple and sensitive approach for determination of selenium in thioridazine hydrochloride. Under optimized conditions, detection limit was 0.2 μg/L and repeatability of the method expressed by relative standard deviation (RSD) for selenium was 2.5 % at 30 μg/L and 9.2 % at 0.5 μg/L and also, the calibration curve was linear over the range of 0.2-30.0 μg/L (R2 = 0.9966, P < 0.0001).